1991
DOI: 10.1097/00006842-199111000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fat and cholesterol on social behavior in monkeys.

Abstract: We report here on the social behavior of 30 adult male cynomolgus monkeys, maintained in social groups of five animals each and assigned for 22 months to one of two dietary conditions: a) "luxury"--relatively high fat, high cholesterol (43% calories from fat, 0.34 mg cholesterol/Calorie of diet); or b) "prudent"--relatively low fat, low cholesterol (30% calories from fat, 0.05 mg cholesterol/Calorie of diet). The dietary manipulation resulted in higher total serum cholesterol (TSC) and lower high density lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(75 citation statements)
references
References 0 publications
6
68
0
1
Order By: Relevance
“…With regard to cholesterol, the findings in this study are similar to those in previous studies, which suggested a link between lower cholesterol and violence to others (Virkkunen, 1983;Kaplan et al, 1991;Muldoon et al, 1992;Mufti and Arfken, 1998;Hillbrand and Spitz, 1999;Golomb et al, 2000;Agargun et al, 2002;Repo-Tiihonen et al, 2002) and violent suicide (Engelberg, 1992;Vevera et al, 2003). The findings with respect to apolipoproteins A1 and B and violence are new.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…With regard to cholesterol, the findings in this study are similar to those in previous studies, which suggested a link between lower cholesterol and violence to others (Virkkunen, 1983;Kaplan et al, 1991;Muldoon et al, 1992;Mufti and Arfken, 1998;Hillbrand and Spitz, 1999;Golomb et al, 2000;Agargun et al, 2002;Repo-Tiihonen et al, 2002) and violent suicide (Engelberg, 1992;Vevera et al, 2003). The findings with respect to apolipoproteins A1 and B and violence are new.…”
Section: Discussionsupporting
confidence: 89%
“…This includes the serotonergic receptors and hence may lead to reduced central serotonergic activity. This was the hypothesis proposed by Kaplan et al (1991), Engelberg (1992) and Hillbrand et al (2000) to explain the role of lowered cholesterol in aggression.…”
Section: Discussionsupporting
confidence: 60%
“…[2][3][4][5][6][7][8] In addition, experimental studies have shown an increase in violent behavior in monkeys assigned to low-cholesterol diets. 36,37 Human and animal research indicates that low or lowered cholesterol levels may reduce central serotonin activity, which in turn is causally linked to violent behaviors. 4,38 Therefore, members of a family who inherit hypocholesterolemia might be expected to be prone to violent behavior.…”
Section: Discussionmentioning
confidence: 99%
“…39 On the other hand, chronically low baseline cholesterol levels may have deleterious CNS eects, 40 and have been found in animal studies to increase aggression. 41 Three large treatment studies have failed to ®nd increased nonillness deaths or signi®cant emotional distress in their treatment arms. However, they also have methodological limitations relevant to this matter.…”
Section: ±21mentioning
confidence: 99%